The Truly Marvellous Proof For n=4 (Global Journal of Science Frontier Research, 2017)
The truly marvellous proof of the Fermat’s Last Theorem for n=4.
Keywords: diophantine equations; diophantine inequalities; fermat equation; greatest common divisor; newton binomial formula